KEANEKARAGAMAN JENIS ROTAN DI KAWASAN HUTAN PRODUKSI DESA SALUKAIA KECAMATAN PAMONA BARAT KABUPATEN POSO - Perusu, Onesimus; Harijanto, Herman; S, Sustri (Universitas Tadulako, 2019)
Rattan is a plant that lives in clumps or singles and is classified into the family Arecaceae / Palmae. Determination of the type of rattan can be through identification based on the morphological character of plant organs. Classification of types of rattan is usually based on the equality of characteristics possessed by each type. Ecologically, rattan thrives in various places, both lowlands and highlands, especially in humid areas such as river banks. This study aims to determine the diversity of rattan species in the production forest area of Salukaia Village, Pamona Barat District, Poso Regency. The study was conducted in December 2015 - January 2016. This study used a survey method to select or place plots deliberately made in places where rattan was found (purporsive sampling). The number of observation lanes is 1 lane with a length of lane 1000 m and width 20 m, then a plot of 20x20 m is made. Along the observation track 30 plots were made. The data obtained were analyzed to determine density, frequency, index, importance value (INP) and diversity index. From the results of the study found 9 (nine) types of rattan namely Kuyuwi rattan (Daemonorops robusta Becc.), Tida Lingka rattan (Daemonorops sp.), Uban rattan (Calamus sp.), Hoa rattan (Calamus ornatus var. Celebicus Bl), rattan rattan (Daemonorops sp.), Uban rattan (Calamus sp.), Hoa rattan (Calamus ornatus var. Celebicus Bl), rattan rattan Bottle Tungka (Calamus inops Becc.), Laru rattan (Calamus orthostachyus Becc.), Silaya rattan (Daemonorops lamprolepsis Becc.), Batang rattan (Calamus zollingerii Becc.), And Ronti rattan (Calamus leptostachys Becc.). The dominant type of rattan at the study site was Kuyuwi (Daemonorops robusta Becc.). The level of diversity of rattan species is classified as being abundant with a value of 1.91.Keywords: Rattan Species Diversity, Production Forest Areas